Management of Creative and Unconventional Talents - Brelih, Eli; Vukovič, Goran (Izzivi managementa talentov, 2025)
Personal talent can manifest itself in different ways over time, which is why we attach great importance to the management of one's own talent or talents. In this chapter, we discuss the path of developing an individual's personal talent, which turned into a business opportunity. Based on interdisciplinary insights from art and talent management, we offer an understanding of the intersection of personal talent and business development. We show a family's insight into experiencing and recognizing their child's talents, nurturing and developing them, and how they later manifested into a different direction of art, which became an excellent business opportunity. Through a personal narrative, we explore the transition from drawing to tattooing, shedding light on the processes, influences and motivations that shaped this evolution. In a case study, we emphasize the interaction between innate talent, family influence and personal passion in promoting artistic growth and diversification.